1987
DOI: 10.1111/j.1365-2036.1987.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an enteric‐coated delayed‐release 5‐aminosalicylic acid tablet in patients with inflammatory bowel disease

Abstract: SUMMARY Gastrointestinal transit of an enteric coated delayed release 5‐aminosalicylic acid tablet radiolabelled with III indium has been monitored in a total of 13 patients with Crohn's disease and ulcerative colitis. More than 70% of the tablets disintegrated in the small intestine, on average 3.2 hours after emptying from the stomach. Dispersed preparation was detected in the proximal colon of all the patients, except one with an ileostomy. Mean peak plasma concentrations of 5‐aminosalicylic acid and its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…Last, the type of 5-ASA preparation (eudragit-L-coated) and the dose (0.5g TID) may have caused insufficient mucosal concentrations in the distal colon 28. In fact, this preparation has been shown to release the drug in the ileocaecal region 29. More delayed-release preparations such as MMX-mesalazine and once-daily administration of a higher dose (above 2 gram;30) may have led to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the type of 5-ASA preparation (eudragit-L-coated) and the dose (0.5g TID) may have caused insufficient mucosal concentrations in the distal colon 28. In fact, this preparation has been shown to release the drug in the ileocaecal region 29. More delayed-release preparations such as MMX-mesalazine and once-daily administration of a higher dose (above 2 gram;30) may have led to different results.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, colonic transit has been shown to be significantly faster in patients with active ulcerative colitis than in healthy subjects (Hardy et al, 1987;Larouche et al, 1995). A marked asymmetry in the distribution of amberlite resin was observed in the large intestine in healthy volunteers, with 69% in the proximal colon and 31% in the distal colon.…”
Section: Disease Can Affect Ileo-colonic Transit and Deliverymentioning
confidence: 93%
“…Patients with irritable bowel syndrome often have accelerated intestinal transit, particularly through the proximal colon (Vassallo et al, 1992). Patients with active ulcerative colitis have also been found to have significantly faster small intestinal transit and colonic transit than controls (Hebden et al, 2000), contradicting results obtained by others (Hardy et al, 1987). It has been reported that many patients that underwent an ileocaecal resection (Munkholm et al, 1993) showed a shorter dosage form stagnation at the ileocaecal junction, thereby reducing the overall small intestinal transit time (Fallingborg et al, 1998).…”
Section: Gastrointestinal Transit Of Dosage Formsmentioning
confidence: 94%
“…The most widely used systems for delivery of mesalamine generally dissolve at pH >6, releasing the drug into the terminal ileum or the colon. [17][18][19] Ethylcellulose-coated microgranule formulations consist of 5-aminosalicylic acid (5-ASA) microgranules encapsulated within Table 1. a semipermeable membrane of ethylcellulose designed for controlled release.…”
Section: Oral Aminosalicylate Formulationsmentioning
confidence: 99%